Control and optimization with differential-algebraic constraints - Biegler, Lorenz T.; Campbell, S. L.; Mehrmann, V. L. 1955- (Society for Industrial and Applied Mathematics, 2012)
Differential-algebraic equations are the most natural way to mathematically model many complex systems in science and engineering. Once the model is derived, it is important to optimize the design parameters and control it in the most robust and efficient way to maximize performance. This book presents the latest theory and numerical methods for the optimal control of differential-algebraic equations. The following features are presented in a readable fashion so the results are accessible to the widest audience: the most recent theory, written by leading experts from a number of academic and nonacademic areas and departments; several state-of-the-art numerical methods; and real-world applications.
Keywords: Differential-algebraic equations.; Control theory.; Mathematical optimization.; elektronické knihy; electronic books